Understanding the Perpetuation of Inequalities in Brazilian K-12 Public and Private Schools from a Historical Perspective - Ana Lucia Mendonca (Educational Considerations, 2020)
Brazilian education has specific cultural and regional traits that infuse the school settings and vast inequalities that go beyond cultural and socioeconomic levels. All that contributed to creating two different school settings: the private and the public. The purpose of this article is to understand from a historical perspective how policies and laws were developed throughout different political periods and how they contributed to the formation of the educational setting in Brazil.
Keywords: Brazilian Education; public school; private school; inequalities